2020
DOI: 10.3897/phytokeys.157.32427
|View full text |Cite
|
Sign up to set email alerts
|

Genetic delimitation of Oreocharis species from Hainan Island

Abstract: Hainan Island harbours an extraordinary diversity of Gesneriaceae with 14 genera and 23 species, amongst which two species and one variety are recognised in the genus Oreocharis. These three Oreocharis taxa are all Hainan-endemics and show a complex geographical distribution pattern with considerable morphological intermixtures. In this study, we combined DNA (nuclear ITS sequences and cpDNAtrnL-trnF and ycf1b) to evaluate genetic delimitation for 12 Oreocharis populations from the island, together with morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Our former study showed the new species O. jasminina and the three other Hainanendemic taxa are homologous, indicating these species in Hainan Island had a common origin (Ling et al 2020). The new species is only found on mountain tops higher than 1200 m in two mountains, Mt.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Our former study showed the new species O. jasminina and the three other Hainanendemic taxa are homologous, indicating these species in Hainan Island had a common origin (Ling et al 2020). The new species is only found on mountain tops higher than 1200 m in two mountains, Mt.…”
Section: Discussionmentioning
confidence: 74%
“…One nuclear ribosomal DNA (nrDNA) sequence, the ITS region comprising spacer 1, the 5.8S gene and spacer 2 (White et al 1990) and one chloroplast DNA (cpDNA) intron-spacer region trnL-trnF (Taberlet et al 1991) were used in this study. Laboratory procedures followed Ling et al (2020) and newly-acquired sequences were deposited in GenBank (Table 2).…”
Section: Taxonomic Sampling Dna Extraction and Molecular Markersmentioning
confidence: 99%
See 3 more Smart Citations